Cerebral processing of pain in school-aged children with neonatal nociceptive input: An exploratory fMRI study - Hohmeister, Johanna; Kroll, Alexander; Wollgarten-Hadamek, Iris; Zohsel, Katrin; Demirakça, Süha; Flor, Herta; Hermann, Christiane U. (Pain, 2010)
Due to maturation-related plasticity of the developing nociceptive system, neonatal nociceptive input, as induced by medical procedures in the neonatal intensive care unit (NICU), may cause long-term alterations in pain processing. Using functional magnetic resonance imaging, this study investigated the cerebral pain response in school-aged children and adolescents (11-16 yr) with experience in a NICU after preterm (≤31 weeks gestational age, N = 9) or fullterm birth (≥37 weeks gestational age, N = 9) as compared to fullterm control children without early hospitalization (N = 9). NICU children had been recruited retrospectively among former patients of the Children's University Hospital Mannheim. All children had participated in our previous studies [46,49] entailing psychophysical measurements. In response to tonic (30 s) heat stimuli of individually adjusted moderate pain intensity, which were of comparable temperature across groups, the preterm but not the fullterm NICU children exhibited significant activations in a number of brain regions (thalamus, anterior cingulate cortex, cerebellum, basal ganglia, and periaquaeductal gray) that were not significantly activated in controls. The preterms showed significantly higher activations than controls in primary somatosensory cortex, anterior cingulate cortex, and insula. This exaggerated brain response was pain-specific and was not observed during non-painful warmth stimulation. Preterms’ continuous pain ratings revealed a tendency for increased sensitization within and a lack of habituation across trials. In highly vulnerable children such as preterms, neonatal nociceptive input may, aside from other neurodevelopmental consequences, persistently increase the gain within pain pathways.